ASSESSING THE FAN COOLING SYSTEM FOR HIGH-SPEED SEWING MACHINE AND ITS ACCEPTABILITY - Ellen S. Cabalquinto, Maria (PT ANTIS INTERNATIONAL PUBLISHER, 2026)
Objective: This research assessed the development and acceptability of the fan cooling system for the effective operation in the sewing process at Cebu Technological University-Tuburan Campus, Tuburan, Cebu during the academic year 2024-2025 for technology diffused adption. Method: This research study utilized quantitative research using applied with the use of descriptive method to assess the system acceptability of a technology infusion in the fan cooling system for the effective operation in the sewing process. The respondents of the study included the total population consisting of two types of respondents, such as experts and nonexperts inside and outside of the institution that includes instructor students and small-scale sewers. Results: Findings from experts and non-experts consistently indicate that the system is highly acceptable (HA) across all aspects, with an overall factor average mean of 4.75. The highest-rated aspect, perceived ease of use (4.78 HA), underscores the system's seamless integration and intuitive operation, while perceived usefulness (4.74 HA) highlights its efficiency in preventing overheating and optimizing energy consumption. Behavioral intention to use (4.73 HA) received the lowest score, though still highly acceptable, suggesting that while users recognize its benefits, external factors may influence adoption. Actual usage (4.75 HA) further supports that the system meets performance expectations, enhances reliability, and contributes to a safer working environment. The findings demonstrate that the fan cooling system is a highly effective and user-friendly enhancement for sewing machines. Novelty: While users acknowledge the cooling system’s contribution to safety, efforts should be made to further highlight and enhance this aspect.